Development of Interactive Video Tutorial Media in Vocational Learning for Children with Special Needs with Mild Mental Requirements: Pengembangan Media Video Tutorial Interaktif dalam Pembelajaran Vokasi Anak Berkebutuhan Khusus Tunagrahita Ringan - ratih agustin wulandari (Perkumpulan Doktor Indonesia Maju (PDIM), 2023)
This research was motivated by the discovery of obstacles in developing low vocational competence for children with special needs for mild mental retardation, in making souvenirs so that there is a need for effective learning strategies and media to improve the skills of mild mentally retarded children so that they are proficient in making souvenirs, so that this can be a provision for children in the future. future and can be competent in the world of work. The purpose of this study was to describe interactive multimedia blueprints based on video tutorials in learning the vocational skills of children with mild special needs, and to determine the feasibility of interactive multimedia based on video tutorials. The type of research used is Research and Development, using the Assure development model. This research involved fifth semester students of Informatics Engineering, Faculty of Computer Science, Dharmas Indonesia University. Based on the results of data analysis obtained from the aspect of content feasibility, which was carried out by content experts, it showed that the product was in accordance with the Learning Plan. Tests on the aspects of appearance, graphics, program operation and grammar carried out by media experts obtained calculation results of being in good qualification. Tests on aspects of learning, curriculum and interface design carried out by learning design experts obtained calculation results of being in good qualifications.